Biomechanical analysis of cycling position in elite cyclist - Prins, T. (2024)
Winning a track sprint cycling race can often come down to a fraction of a second. In 2016 at the Rio Olympic Games, the Australian men`s sprint team lost to Great Britain by 0.102 seconds. Therefore, it is essential that cycling conditions have been optimised to enable the cyclist to output maximum pedal force. The position of the cyclist on the bicycle has proven to have the most significant effect on pedal force production.